Effect of peripheral retinal ablation with cryotherapy versus diode laser photocoagulation on axial length in the growing rabbit eye - Axer‐Siegel, R (BMJ Group, 2006)
AIMS: To evaluate and compare the effects of peripheral retinal cryotherapy and diode laser photocoagulation on axial length, anterior chamber depth, and lens thickness in developing rabbit eyes. METHODS: 26 eyes of 6 week old Abbit rabbits were randomly assigned to undergo laser photocoagulation or cryotherapy of the peripheral retina. Eight eyes of four untreated rabbits served as controls. Biometric and intraocular pressure measurements were performed at 0, 5, and 10 weeks after treatment. RESULTS: Five rabbits died, leaving 10 rabbits (20 eyes) in the study group and two (four eyes) in the control group. Average axial lengths for the control, laser treated, and cryo treated eyes were 15.72 mm, 16.08 mm, and 16.11 mm, respectively, at baseline and 17.48 mm, 18.09 mm, and 19.4 mm, respectively, at 10 weeks after treatment (p = 0.028, paired Wilcoxon test). Anterior chamber depth increased from 2.2 mm to 2.5 mm in both treatment groups, and from 2.14 mm to 2.28 mm in the control group. Lens thickness averaged 5.11 mm in the control group and 5.38 mm in the treatment groups before treatment, and 6.34 mm, 6.31 mm, and 6.38 mm, respectively, 10 weeks after treatment. CONCLUSIONS: Peripheral retinal cryotherapy causes a significantly greater elongation of the eye compared to diode laser photocoagulation in a rabbit model.